Alpinetin protects against iron overload related osteoarthritis via NRF2/HO-1 pathway - Dongling Cai; Zhaofeng Pan; Shaocong Li; Qi He; Baihao Chen; Miao Li; Jiacong Xiao; Fancheng Wan; Haibin Wang; Chi Zhou (PLoS ONE, 2025)
Context Alpinetin(APT) is a natural product with anti-inflammatory and antioxidant effects. Iron overload has been recognized in recent years as a new way to exacerbate osteoarthritis. Objective This study evaluated the effects of ATP on iron overload related osteoarthritis. Materials and methods C57BL/6J mice were randomly allocated to five groups as follows (n = 10 mice each): (1) sham; (2) destabilized medial meniscus(DMM); (3) DMM + ID; (4) DMM + ID + APT-L (50 mg/kg APT gavage daily); (5) DMM + ID + APT-H (100 mg/kg APT gavage daily). The chondrocytes treated by FAC (100μM) were used as an in vitro model of iron overload and the effect of APT was observed. Flow cytometry, fluorescence microscopy, Western blot, qRT-PCR and micro-CT were used to detect the mechanism of action of the APT. Result Our studies showed that APT improved the viability of chondrocytes induced by iron overload. APT can reduce apoptosis of chondrocytes (19.41 ± 2.12% vs. 9.82 ± 1.74%). Furthermore, APT was found significantly attenuated ROS accumulation (2.04 ± 0.31 vs. 1.44 ± 0.15-fold) of chondrocytes through upregulating antioxidant genes NRF2 (1.18 ± 0.13 vs. 1.55 ± 0.17-fold) and HO-1 (1.27 ± 0.15 vs. 1.77 ± 0.20-fold). In vivo experiments revealed that APT attenuated cartilage damage (OARSI score 5.75 ± 1.32 vs. 3.75 ± 0.96) and subchondral bone proliferation in iron overload osteoarthritis mice. Conclusions Our results show that APT can attenuate iron overload-induced cartilage damage in vivo and in vitro via the NRF2/HO-1 pathway. We demonstrated for the first time that APT has promising applications in iron overload diseases.